2012
DOI: 10.1089/g4h.2011.0025
|View full text |Cite
|
Sign up to set email alerts
|

Exergaming, Exercise, and Gaming: Sharing Motivations

Abstract: Health professionals view exergame technologies as an alternative tool in therapeutic treatments and the promotion of physical activity. There is a growing body of work addressing the health benefits of exergaming; however, there is limited knowledge concerning user experience in this new context. If we aim to encourage participation in exergaming, we must first understand why gamers currently play exergames. Exergaming refers to the computer games that require players to perform some level of physical exertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…Key motivations for playing exercise games were perceptions of enjoyment, feeling better afterwards and participation in a social context [21]. This is fully in line with our results, which demonstrated that during the 12-week exercise game intervention, diabetes-dependent impairment decreased, and mental health, subjective wellbeing and quality of life improved significantly.…”
Section: Discussionsupporting
confidence: 88%
“…Key motivations for playing exercise games were perceptions of enjoyment, feeling better afterwards and participation in a social context [21]. This is fully in line with our results, which demonstrated that during the 12-week exercise game intervention, diabetes-dependent impairment decreased, and mental health, subjective wellbeing and quality of life improved significantly.…”
Section: Discussionsupporting
confidence: 88%
“…The definition states that games should consist of four main components, namely: (1) a goal to achieve, (2) rules to follow, (3) a feedback system for people to track their progress and (4) the voluntary acceptance of the three first elements. Hence, the selected studies meet the following definition adopted from [21] [20] [13]: "'a digital game that require players to (voluntary) perform physical exertion to play and where the game has specific goals, rules, and a feedback mechanism" Further, we denote by Quasi-medical the type of different gamified systems and exergames that were designed and developed for therapeutic and rehabilitation purposes.…”
Section: Figure 2 Flowchart Of Literature Review Processmentioning
confidence: 99%
“…Exergames (entertaining exercise video games) are cited in the literature as a means of encouraging individuals to engage in physical activity. Key elements that encourage individuals to participate in exergames include perceptions of enjoyment, feeling better after a session, and participation within a social context (Osorio, Moffat, & Sykes, 2012). There is a growing body of work addressing the health benefits of Wii exergames in older adults, such as improving balance, mobility, and muscle strength (Chao, Scherer, Wu, Lucke, & Montogomery, 2013;Jorgensen, Laessoe, Hendriksen, Nielsen, & Aagaard, 2013), decreasing depressive symptoms, as well as improving cognitive performance and mental healthrelated quality of life (Rosenberg et al, 2010).…”
Section: Introductionmentioning
confidence: 99%